ANALISIS DAMPAK PENGEMBANGAN PARIWISATA PANTAI MANIKIN DALAM MENINGKATKAN KESEJAHTRAAN EKONOMI MASYARAKAT KELURAHAN TARUS KABUPATEN KUPANG NUSA TENGGARA TIMUR - Missa, Vebriaty Veronika; Ballo, Fransina Wehelmina; Tiwu, Maria Indriyani Hewe (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The current development of Manikin Beach as a tourist destination is almost optimal, this has an impact on increasing the level of community welfare. The aim of this research is to determine the impact of developing Manikin Beach tourism on the socio-economic life of the Tarus Village community, as well as supporting and inhibiting factors for tourism development that will have an impact. on the economy of the Tarus community. This research uses a descriptive method with a qualitative approach and the data sources used by researchers are primary data and secondary. Data collection techniques through interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the research show that the development of Manikin Beach tourism has an impact on the economic welfare of the people of Tarus Village who are around the tourist attraction. The significant impact felt by the people of Tarus Village is the opening of business opportunities, these business opportunities consist of culinary businesses and grocery stores. The income received by the community from the results of the business they run can meet family needs, education costs and health costs. Supporting factors for tourism development in improving the economic welfare of the Tarus Village community are tourist attractions, facilities and services, ease of reaching tourist locations, hospitality offered and tourist attraction fees. Meanwhile, the inhibiting factors are the lack of human resources (HR) and lack of supervision from the government. Keywords: Impact, Development, Inhibiting Factors, Manikin Beach, Supporting Factors.